CHALLENGES IN IMPLEMENTING OPTIONAL CLAUSES IN INTERNATIONAL SALE OF GOODS AGREEMENTS(CHALLENGES IN APPLYING CHOICE CLAUSES IN INTERNATIONAL SALE OF GOODS CONTRACTS) - Priscillia Putri Feliana (CV. RADJA PUBLIKA, 2025)
This research analyzes the application of choice of law and choice of forum clauses in international sale of goods contracts by Indonesian courts. It highlights the inconsistencies in juridical decisions which often confuse or ignore these concepts, causing legal uncertainty. Using a juridical-dogmatic method, the study explores four contractual clause conditions: both clauses present, only choice of law, only choice of forum, and neither. By examining several court decisions, the study reveals conceptual confusion and misapplication of private international law (PIL). It concludes that courts should distinguish these clauses clearly and apply relevant PIL principles. The study recommends ratifying the Draft Bill on PIL by adopting HCCH principles to guide judges in transnational disputes.